Pengaruh Tingkat Pengetahuan, E-samsat, Sanksi Pajak, dan Pelayanan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Efendy Tjia Chun Che; Handra Tipa (Komunitas Dosen Indonesia, 2023)
Taxes are the main resource of revenue, especially in the revenue budget and the state budget. We are optimistic the rupiah will still be under pressure, he said. Taxes are a means of paying the people to the state, and the people have a legal obligation to be able to pay off some of their wealth immediately. The purpose at this study is to examine how the level of knowledge, e-samsat, tax penalties and services can affect the taxing compliance of motor vehicles. The ressearch methode at this study is the deisgn of quantitative research design, with primary and secondary data sources. The population in the study involved motorized taxes in the 442 city of batam. In the study a large sample decipherment using the slovin formula with the number of 400 respondentts. In this study the method of collecting samples used is a combination of a non-sampling and an estimated forecasts. Data analysiss techniques use valification tests, religious tests, normality tests, multicolosynticizing tests, linear regression tests, determinations coefficient analysis (R2), test t and test f. studies indicate that knowledge levels, e-samsat, tax sanctions and service simultaneously have a positife and significant impact on motor vehicle taxing